2012
DOI: 10.1002/jbm.b.32646
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of drug microparticles with self‐assembled Fe3O4/alginate hybrid multilayers for targeted controlled release

Abstract: The magnetic-targeted drug-delivery system was developed with the Fe(3)O(4) nanoparticles as the self-assembling material to form the hybrid multilayer shells. Layer-by-Layer stepwise self-assembly of the natural polyelectrolytes sodium alginate and the Fe(3)O(4) nanoparticles was used to create the magnetic hybrid multilayers around drug microparticles (~400 nm in diameter) for the purpose of targeted controlled release. The obtained drug microparticles encapsulated with hybrid multilayers were characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In recent years, many developments in the drug delivery system have been focusing on the target release [6], controlled release [7], extended time of drug action [8], and so on. For ibuprofen, several methods for the preparation of drug carriers have been reported to solve the issues appearing in the direct use of drug.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many developments in the drug delivery system have been focusing on the target release [6], controlled release [7], extended time of drug action [8], and so on. For ibuprofen, several methods for the preparation of drug carriers have been reported to solve the issues appearing in the direct use of drug.…”
Section: Introductionmentioning
confidence: 99%
“…LbL assembly provides an opportunity to form a nano-thick coating in a controllable manner on the surfaces of variable curvature and size from interacting oppositely charges polyelectrolyte components (Shutava et al, 2012; Lvov, 2000; Sukhorukov, 2002; De Geest et al, 2009; Schneider and Decher, 2004; Chodanowski and Stoll, 2001; Li et al, 1994; Kong et al, 1998; Vertegel et al, 2004; Mu et al, 2012; Lu and Liu, 2012). Anchored to the core surface, the thin shell of hydrophilic polyelectrolytes allow exchange of excipients used on the core preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Additional beneficial properties of the coating may be gained by including nanoparticles in the multilayer shell . For example, inclusion of paramagnetic particles could potentially enable magnetic‐driven delivery of the drug cores to the target disease area.…”
Section: Coating Materials and Lbl Methodologymentioning
confidence: 99%
“…For example, inclusion of paramagnetic particles could potentially enable magnetic‐driven delivery of the drug cores to the target disease area. For example, preliminary experiments demonstrated that applying a magnet to a vessel containing dipyridamole particles coated with shell incorporating superparamagnetic iron (II, III) oxide nanoparticles resulted in their clustering, which suggest their potential for magnetic guidance in vivo …”
Section: Coating Materials and Lbl Methodologymentioning
confidence: 99%